A Novel Partial Thermal Image Encryption Scheme Based on Multiple Chaotic Systems - B S, Lokesh; M B, Dr. Manjunatha (International Journal of Engineering and Technology, 2018)
In this paper, proposed an novel partial encryption scheme for protecting thermal images during transmission. The adopted technique having pixel level and bit level permutation process. To reduce time and computational complexity, an partial encryption technique is adopted. Arnold cat map technique involved in the pixel level permutation process to decrease correlation of original image. The proposed scheme selects only higher four binary planes for the bit level shuffling process. Where this process consists of row and column wise circular shift operation with the help of pseudo random numbers generated from chaotic map system. Mixing of binary planes of the thermal image will leads to prevent the differential attacks. Experimental results shows that proposed scheme exhibits good performance in terms entropy, NPCR and the speed of system.